Directors’ remuneration, firm performance and political connection: evidence from state-owned enterprise (SOE) in Malaysia - Marziana Madah Marzuki; Roslina Salwani Haji Shukri (Penerbit Universiti Kebangsaan Malaysia, 2019)
The objective of this paper is to examine the relationship between directors’ remuneration and firm performance among state-owned enterprise (SOE) in Malaysia. In addition, we examine whether board size and government’s role moderate the relationship between directors’ remuneration and firm performance in SOE. Using panel data regression model on 118 firm-year observations of state-owned enterprise in Malaysia from 2011 to 2013, this study finds there is positive relationship between directors’ remuneration and firm performance. The result provides supports that directors’ remuneration acts as incentive to board of directors to perform their monitoring task. The result also indicates that larger board size and government play an important role in enhancing firm performance of state-owned enterprise in Malaysia. Nevertheless, when we interact both variables with directors’ remuneration, the result indicates that larger board size and political connected directors moderate the positive relationship between firm performance and directors’ remuneration. Our result provides evidence that the interaction between directors’ remuneration and board size as well as political connected directors explain firm performance among state owned enterprise in Malaysia.